Biimidazole diamide anion binding agents - Allen, William E.; Causey, Corey (My University, 2006)
Biimidazole diamide compounds that are useful for binding anions such as sulfate are described, along with the use thereof for purposes such as extracting anions from a waste stream and/or detecting anions.